Free vibration and buckling of bidirectional functionally graded sandwich plates using an efficient Q9 element - Le, Cong Ich; Tran, Quang Dung; Pham, Vu Nam; Nguyen, Dinh Kien (Vietnam Journal of Mechanics, 2021)
Free vibration and buckling of three-phase bidirectional functionally graded sandwich (BFGSW) plates are studied in this paper for the first time by using an efficient nine-node quadrilateral (Q9) element. The core of the sandwich plates is pure ceramic, while the two skin layers are of a three-phase bidirectional functionally graded material. The element is derived on the basis of the Mindlin plate theory and linked interpolations. Fundamental frequencies and buckling loads are computed for the plates with various boundary conditions. Numerical result shows that convergence of the linked interpolation element is faster compared to the conventional Lagrangian interpolation Q9 element. Numerical investigations are carried out to highlight the influence of the material gradation and the side-to-thickness ratio on the vibration and buckling behaviour of the plates.